2020
DOI: 10.1111/nph.16493
|View full text |Cite
|
Sign up to set email alerts
|

Current research frontiers in plant epigenetics: an introduction to a Virtual Issue

Abstract: Link to the Virtual Special Issue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
(68 reference statements)
1
15
0
2
Order By: Relevance
“…Epigenetic mechanisms more broadly (including DNA methylation, histone modification or RNA interference) have well-documented roles in response to multigenerational abiotic stresses in some species (Lämke & Bäurle, 2017). Eriksson, Szukala, Tian, and Paun (2020) (Barnes et al, 1997;Nakamura et al, 2011). Although the mechanistic basis of this adaptation has not been well studied, a loss of plasticity in selected traits that are initially responsive to elevated [CO 2 ] has been observed in CO 2 spring plant populations, in support of our own findings (Barnes et al, 1997;Nakamura et al, 2011).…”
Section: Correlations Between Genetic and Methylome Variation Only supporting
confidence: 86%
“…Epigenetic mechanisms more broadly (including DNA methylation, histone modification or RNA interference) have well-documented roles in response to multigenerational abiotic stresses in some species (Lämke & Bäurle, 2017). Eriksson, Szukala, Tian, and Paun (2020) (Barnes et al, 1997;Nakamura et al, 2011). Although the mechanistic basis of this adaptation has not been well studied, a loss of plasticity in selected traits that are initially responsive to elevated [CO 2 ] has been observed in CO 2 spring plant populations, in support of our own findings (Barnes et al, 1997;Nakamura et al, 2011).…”
Section: Correlations Between Genetic and Methylome Variation Only supporting
confidence: 86%
“…Studies have revealed that epigenetic process like DNA methylation, histone modifications, and small RNAs play an important role in the different stages of seed development, including embryogenesis, seed maturation, and germination (Greaves et al 2015;Wang and Köhler 2017;Eriksson et al 2020). This contribution of epigenetic regulation has also been reported in the fitness of F 1 hybrids and heterosis or hybrid vigour (Groszmann et al 2013;Greaves et al 2015).…”
Section: Maternal Effects On F 1 Germinationmentioning
confidence: 99%
“…Наголошується, що уявлення про пластичність як загальне біологічне явище потребує особливої уваги до її екологічних аспектів, оскільки припускається істотний вплив пластичності організмів на стабільність і локальне різноманіття популяцій та угруповань шляхом впливу на перенос енергії, вуглецеві цикли, число трофічних рівнів, кругообіг поживних речовин та первинну продуктивність. Підкреслюється перспективність досліджень пластичності в екологічному аспекті для подальшого розуміння як механізмів відповідей організмів на дію чинників абіотичного та біотичного оточення, так і впливу цих відповідей на взаємовідношення організмів між собою та довкіллям (Sultan, 2003;Miner et al, 2005;Aubin-North, Renn, 2009;Dubyna, Kordyum, 2015;Kordyum, Dubyna, 2019;Eriksson et al, 2020).…”
Section: фенотипічна пластичністьunclassified
“…Сьогодні загальноприйняте визначення епігенетики як області дослідження змін у функціонуванні генів, які успадковуються через мітоз, можливо, мейоз, але не включають змін у послідовності нуклеотидів ДНК. Сучасні ідеї щодо епігенетичних систем регуляції експресії генів висвітлено в численних статтях та оглядах (Grant-Dowto, Dickinson, 2005;Zhang, 2008;Tomilin, 2009;Kinoshita, Seki, 2014;Köhler, Springer, 2017;Eriksson et al, 2020). Тому ми лише нагадаємо, що як складові епігенетичних систем регуляції генної експресії розглядаються метилування/деметилування ДНК, модифікації гістонів і малі некодуючі РНК (інтерферуючі РНК, мікроРНК).…”
Section: епігенетична регуляція генної експресіїunclassified